Brain ultrasound rehearsal before surgery: A pilot cadaver study. Issue 8 (26th July 2017) - Giussani, Carlo; Riva, Matteo; Djonov, Valentin; Beretta, Simone; Prada, Francesco; Sganzerla, Erik
Abstract : It has been shown that brain ultrasonography (US) is an efficient tool for improving three‐dimensional (3D) spatial orientation during neurosurgical interventions. However, it necessitates specific training as it is highly operator‐dependent. To date, neurosurgeons have relied solely on intraoperative practice to improve their mastery of brain US; this has obvious limitations. Herein, we consider whether a study of brain US on human cadavers could enable a training platform for neurosurgeons and residents to be developed. Standard two‐dimensional (2D) brain US was performed on two human cadavers (one fresh‐frozen and one Thiel‐prepared) through left frontoparietal, left frontal, right temporal, and left parietal craniotomies. US workflow and image quality were assessed in both preparations. It was possible to assess US in both cadaver preparations; however, the specimen prepared with Thiel‐fixation performed better, with superior image quality and specimen usability at room temperature. US images were obtainable through all surgical corridors with the main intracranial anatomical landmarks easily identifiable. US of cadaveric brains is feasible and delivers good quality results. This technique could allow neurosurgeons to develop the expertise required for a successful clinical application preoperatively. Clin. Anat. 30:1017–1023, 2017. © 2017 Wiley Periodicals, Inc.